Oscillation : bioadéquation et bien-être sont-ils l'avenir d'un progrès durable pour nos enfants ? - Franck Raffegeau; Eric Tromeur (VertigO)
In the coming decades, adaptation to climate change is a critical issue for plant and animal species, especially humans. However, what kind of adaptation we want to go through? Today, the use of the word "adaptation" is confused. The concepts of "adaptation", dynamics development of species, in particular the development of man, and their "dependency relations" seem misunderstood by opinion leaders, policy makers and laymen. Is this adaptation well defined for the well-being of mankind and the progress of societies? In the context of this work, the authors questioned the height of view that humans must achieve to get a better vision of their fate and nature, relational and behavioral development of individuals being a source of well-being and progress indicator. Three different perspectives of the common conception of adaptation in our Western society are addressed: bioadequation, compensation and adaptation. These three perspectives will help to replace the human being as a biological being and animal species living in relationship with other species. So in the context of our dynamic development in urban and suburban areas, this discernment involved in opening the debate on the real abilities of species responses to climate change hazards.